Urinary Concentrating Ability in Women with Asymptomatic Bacteriuria in Pregnancy. Issue 5664 (26th July 1969) - Williams, G. L.; Campbell, H.; Davies, K. J.
Abstract : The incidence of impaired renal concentrating ability in pregnant women with asymptomatic significant bacteriuria is significantly less than previously reported when osmolality readings are performed on every urine specimen obtained during the 24 hours' deprivation of fluids. The concentrating defect is more considerable as pregnancy progresses. The lower the maximum urinary osmolality the more difficult is the treatment of the patient, and the higher the incidence of acute pyelonephritis.